Engineering Disaster Investigation and Recurrence of the Covering Effect in a Petroleum and Gas Station in Seasonally Frozen Soil Region - Xiaohui Liu; Ruiling Zhang; Huyuan Zhang; Kai Wu; Weibin Zhou; Bo Liang; Guang Li (Geofluids)
The impermeable engineering surface layer in the cold regions blocks the water and heat exchange between the foundation soil and the atmospheric environment. Especially in cold areas with significant temperature differences, the moisture in the foundation soil accumulates at the bottom of the structure layer to form a covering effect. This will exacerbate the occurrence of engineering freeze-thaw diseases. This paper conducts a disease survey of the Guanshan oil and gas station site, which is located in a seasonally frozen soil zone. The ponding and freeze-thaw diseases under the concrete cover are analyzed. The formation process of the pot covering effect in the lower part of the concrete surface layer was reproduced through indoor tests. In addition, a water-vapor-heat coupling model of unsaturated soil was established, which quantitatively produced the formation process of silty clay covering under the concrete slab. The results show that (1) in-situ monitoring demonstrated that the water content of the roadbed soil from 0 to 50 cm below the concrete slab gathered significantly, with the water content increasing by 5 to 30%. (2) Under the action of the indoor time-varying covering effect, the moisture content of silty clay will increase with the number of freezing-thawing cycles, with a maximum migration amount of 6%. (3) Seasonal temperature changes lead to the accumulation of water in the subgrade surface, and the maximum accumulation amount is 32%. (4) During the freezing period, the liquid water and vapor water in the subgrade migrate to the surface layer of the subgrade. As a result, the moisture content of the subgrade surface layer increases, while the melting period is the opposite. The above research results can provide theoretical support and scientific countermeasures for engineering design and disease control in cold regions.